Modifikasi Mesin Pencacah Sisa Tanaman Tipe Circular Saw - M. Rizky Fitriansyah; Tri Tunggal; R. Mursidi Mursidi (Universitas Sriwijaya, 2012)
A modified crushing machine made of circular saw was created with differences in some components, they are circular saw arrangement, concave shape, hopper, outlet boot, and source of power. This machine has 130 cm in lenght, 80 cm in height, 28 cm concave diameter, 25 cm of circular saw diameter, 20 cm of circular saw strengthener and 8 hp of diesel engine. Paddy straw was chosen as a trial material to test the performance of the machine. It was chosen because the previous machine did not success to chrush this material. The modified machine was able to run perfectly and crush the paddy straw. A capacity of 19,23 kg/h was reached when the test was done. The result of the crushing process was about 2 cm in length of the paddy straw. The fuel consumption was 0,880 L/h.Keywords : Crushing machine, Paddy Straw, Circular saw